Transitions Between Consciousness and Unconsciousness - Marcus Rothkirch; Guido Hesselmann; Morten Overgaard (Frontiers Media SA, 2021)
Over the last years, a large body of experimental data have been generated in the attempt to understand consciousness and its neural underpinnings. In this respect, particular interest has been paid to the attempt to distinguish between conscious experience and unconscious states which however may still be considered as mental states (e.g., in virtue of their representational nature). This is of course not without reason. A deep understanding of that which specifically characterizes conscious states, including neural correlates and cognitive functions, may crucially inform the ambition of understanding the relation between experience and the physical world. Nevertheless, the question has historically been challenged by the fact that consciousness is available in the first person only – not to other people, including scientists. Different methodological traditions and choices have led to quite different understandings of how conscious and unconscious states relate, and diverse empirical work has been inspired and guided by various cognitive and neurobiological theories of consciousness. The very diverse viewpoints include such different positions as the idea that unconscious states are associated with the very same functional characteristics as conscious states, and the idea that no informational state that is available for action can be completely unconscious. The Research Topic “Transitions between consciousness and unconsciousness” is therefore devoted to this particular question, how to understand the relation and transition between consciousness and unconsciousness. We hope that the reader will find the collected articles both informative and thought-provoking, and that this Research Topic will stimulate the scientific debate.